Development and Validation of a Web-Based Augmented Reality Platform for Educational Applications - Vanzuita, Ana Clara; Santos, Ana Fábia Coelho Dos; Küster, Luis Felipe; Klettenberg, Renan Guilherme; Mondini, Jaqueline; Vahldick, Adilson; Luz, Thalia Lichtenfels Da (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Augmented Reality (AR) reveals itself as a promising technology for education. However, its adoption in public schools faces challenges, such as costs, technical complexity, and the lack of easy-to-use tools for teachers. This article presents EducaAR, a platform with AR Web technologies for the application of augmented books, which means it uses textbook figures as markers to display 3D models. The environment supports four different user profiles, and adapts its visualization according to the profile authenticated in the environment: while the profiles of the teacher, administrator, and developer are viewed in browsers, the student is viewed on mobile devices. The student can answer a multiple-choice questionnaire on the subject addressed in the model viewed. The teacher is able to monitor the performance of students and their access frequency. Developers are responsible for adding the models on the platform and associating them with its respective book’s figure. And the administrator has management roles in the environment. The platform was used by 31 High School students in Biology classes. The models were developed by 15 teams of three students from the Bachelor’s Degree in Software Engineering (BSE) course, who used the platform as a developer profile. In addition, an Acceptance Test was conducted with the two teachers involved in the experiment. The research follows the methodological principles of Design-Based Research (DBR), and the second cycle will be presented in this article. Data collection was conducted using three distinct instruments tailored to each participant group: students completed the MAREEA assessment, teachers responded to the System Usability Scale (SUS), and developers provided feedback through a custom five-question survey. The teachers evaluated the usability of the platform as "Excellent" in all the features tested, but suggested the inclusion of tutorials or training for teachers less familiar with technologies. The results of the analysis with the developers indicate that, in order to implement EducaAR in schools with students creating 3D models, training in simplified tools and the structuring of tasks with progressive complexity are necessary. The students positively evaluated the usability of the platform, reporting high involvement in the activities and increased curiosity for the content. Nevertheless, they showed less confidence in learning more complex concepts, which suggests the adoption of complementary didactic strategies.